Evaluation of Tannery Wastewater Treatment by Integrating Vesicular Basalt With Local Plant Species in a Constructed Wetland System - Alemu, Agegnehu; Gabbiye, Nigus; Lemma, Brook (Frontiers in Environmental Science, 2021)
Tannery wastewater is composed of a complex mixture of organic and inorganic components from various processes that can critically pollute the environment especially water bodies if discharged without treatment. In this study, integrated vesicular basalt rock and local plant species were used to establish a horizontal subsurface flow constructed wetland system and to investigate the treatment efficiency of tannery wastewater. Four pilot units were vegetated with P. purpureum, T. domingensis, C. latifolius, and E. pyramidalis, and a 5th unit was left unvegetated (control). The constructed wetland units in horizontal subsurface flow systems were effective in removing total chromium (Cr), chemical oxygen demand (COD), and 5-day biological oxygen demand (BOD5) from the inflow tannery wastewater. The removal efficiency reached up to 99.38 %, 84.03 %, and 80.32% for total Cr, COD, and BOD5 respectively in the 6 days of hydraulic retention time (HRT). The removal efficiency of total suspended solid (TSS), total phosphorus (TP), and nitrate (NO3-) of the constructed wetland units reached a maximum of 70.59 %, 62.32 %, and 71.23 % respectively. This integrated system was effective for treating tannery wastewater, which is below the Ethiopian surface water standard discharge limit set to BOD5 (200 mg L-1), COD (500 mg L-1), total Cr (2 mg L-1), NO3- (20 mg L-1), TSS (50 mg L-1), and TP (10 mg L-1).